New coralline algae from an extreme habitat in the Conero Riviera (Middle Adriatic Sea) - Annalisa Caragnano; Daniela Pica; Annalisa Falace; Fabio Rindi; Gilda Savonitto; Carlo Cerrano (Società Botanica Italiana onlus, 2020)
Apart from a few pioneering studies, it was only in the twentieth century that new scuba diving technologies allowed the study of the communities of marine caves. The topography and morphology of caves affect both lighting and hydrodynamics, and hence the presence of marine organisms. Data on the phytobenthos of such extreme habitats are rather scarce, particularly for Italian waters. Because of the peculiarity of the hosted biocenoses, the submerged or partially submerged sea caves are among the Priority Habitats listed in the Annex 1 of Directive 92/43/CEE of the Barcelona Convention. Coralline red algae (Corallinophycidae, Rhodophyta) are a major calcifying component of marine ecosystems worldwide, occurring from tropical to polar regions, from the lower intertidal to the deepest euphotic zone. In the upper intertidal, the presence of most species is hampered by their low resistance to abrupt excursions in temperature and salinity and to drying during the low tides. Nevertheless, some more tolerant species occurring in large tide pools in the North Atlantic Ocean, such as Phymatolithon squamulosum, are primarily intertidal thanks to the porosity of the rocks on which they thrive. Along the Sicilian and Calabrian upper intertidal, to the best of our knowledge Phymatolithon lenormandii is the only coralline that has been observed in the “trottoirs” of Lithophyllum byssoides and at the entrance of some marine caves. We report for the first time the presence of two encrusting coralline species on the vertical walls of a semi-submerged marine cave in the Middle Adriatic Sea (Conero Riviera – Italy). The coralline identity was investigated through molecular analyses (psbA, LSU rDNA and cox2,3 sequences) and morpho-anatomical observations. Comparing our DNA sequences with the GenBank database, the coralline algae reveal higher regions of similarity with the sequence of Phymatolithon lamii from Ireland (98.7%) and a Lithophyllum sp. from the Tuscan archipelago (98.1%). The cave, approx. 6 m long and 2 m high above ...